Psychocognitive Factors and Recovery from Hip Fracture : A Real-life Prospective Cohort Study - Jaatinen, Roope (fi=Turun yliopisto|en=University of Turku|, 2023)
The data for this study comprised hip fracture patients aged 65 years or more suffering their first hip fracture and treated in Seinäjoki Central Hospital between 2007 and 2019 (n=2,320). Data were collected on admission, during hospital care, in an outpatient comprehensive geriatric assessment (CGA) 4–6 months post-hip fracture and by telephone interviews after the index fracture. New diagnosed cognitive disorder extracted manually from the electronic patient files was documented in almost one in four patients (23.3%). Cognitive disorders had usually advanced to a moderate to severe stage before diagnosis. Higher age, multiple comorbidities and malnutrition were associated with new cognitive disorders. The array of diagnoses did not differ from general occurrence as Alzheimer’s disease with or without vascular cognitive impairment was the most common diagnosis. Delirium during acute hospital care was a significant predictor of an imminent diagnosis of a cognitive disorder. Depressive mood assessed at the outpatient clinic was associated with poorer physical and cognitive performance, and also with malnutrition. Depressive mood was seldom severe. Fear of falling (FoF) was more common in female patients and in patients with multiple medications in regular use and moreover associated with poorer physical performance. Patients with pre-fracture cognitive disorders reported less FoF than those without. Neither depressive mood nor FoF explained the decreased mobility level, change to more supported living arrangements or mortality in one-year follow-up. Previously undiagnosed cognitive disorders are common in older hip fracture patients. Delirium during hospital care is associated with development of subsequent new diagnoses of cognitive disorders. Depressive mood and FoF are common multifactorial conditions which deserve attention during recovery but do not explain the changes in outcomes one year after the hip fracture. There seems to be significant overlap and co-occurrence of psychocognitive factors in this remarkably heterogeneous population, and thus, CGA should be considered as a standardized protocol throughout the post-hip fracture pathway.

Tutkimuksen tavoitteena oli tutkia lonkkamurtuman jälkeisessä seurannassa todettavia uusia muistisairauksia sekä muiden psykokognitiivisten tekijöiden merkitystä sairaalahoidon ja toipumisen aikana. Aineisto koostui Seinäjoen keskussairaalassa vuosina 2007–2019 hoidetuista yli 65-vuotiaista lonkkamurtumapotilaista (n=2320). Tiedot kerättiin sairaalahoidon aikana, polikliinisessä kokonaisvaltaisessa geriatrisessa arvioinnissa (CGA) 4–6 kuukautta murtuman jälkeen, sekä puhelinhaastatteluilla. Muistisairauteen sairastuminen oli yleistä toipumisen aikana. Sairauden vaihe oli yleensä ehtinyt edetä kohtalaiseen tai vakavaan vaikeusasteeseen ennen diagnoosia. Uutta muistisairautta ennusti korkeampi ikä, komorbiditeetit ja vajaaravitsemus. Todettujen muistisairausdiagnoosien kirjo ei poikennut yleisistä esiintyvyyksistä. Sairaalahoidon aikainen delirium oli selvästi yhteydessä uuteen muistisairauteen. Depressiivistä mielialaa todettiin lähes joka kolmannella ja kaatumisen pelkoa lähes joka toisella potilaalla lonkkamurtuman jälkeisessä CGA:ssa. Depressiivinen mieliala oli yhteydessä huonompaan toiminnalliseen, fyysiseen ja kognitiiviseen suorituskykyyn, sekä vajaaravitsemukseen. Vaikeusasteeltaan depressiivinen mieliala oli harvoin vakavaa. Kaatumisen pelko oli yleisempää naisilla ja monilääkityillä. Kaatumisen pelko liittyi myös heikompaan fyysiseen suorituskykyyn. Potilaat, joilla oli todettu muistisairaus ennen lonkkamurtumaa, kokivat vähemmän kaatumisen pelkoa, kuin potilaat, joilla ei ollut todettua muistisairautta. Depressiivinen mieliala tai kaatumisenpelko eivät yksinään selittäneet heikentynyttä liikuntakykyä, muuttoa tuetumpaan asumismuotoon tai kuolleisuutta vuoden kuluttua murtumasta. Aiemmin diagnosoimattomat muistisairaudet ovat yleisiä iäkkäillä lonkkamurtumapotilailla. Sairaalahoidon aikainen delirium on yhteydessä uusiin lonkkamurtuman jälkeen todettuihin muistisairauksiin. Depressiivinen mieliala ja kaatumisen pelko ovat yleisiä, monitekijäisiä ongelmia, jotka on syytä huomioida kuntoutumisen aikana, mutta eivät yksinään selitä tilannetta vuoden kuluttua murtumasta. Psykokognitiiviset tekijät voivat esiintyvät limittäin tai samanaikaisesti tässä hauraassa potilasryhmässä ja siksi lonkkamurtuman jälkeinen CGA olisi tärkeää saada osaksi standardoitua hoitopolkua.